E-Presence and Monitoring System Based on Face Image Recognition with Local Binnary Pattern Histogram (LBPH) Algorithm - Nurhikma; Abdul Wahid; Jumadi M Parenreng (Program Studi Teknik Komputer, 2024)
Abstract : There are still many attendance systems that are done manually, and some still use paper as an attendance tool. So it is not effective because the data from attendance is easy to manipulate. The purpose of this study is to create attendance by using web-based facial recognition so as to produce e-presence. The accuracy rate of facial sensitivity obtained by this researcher is 90%. This researcher uses the LBPH method to determine the level of accuracy of various lighting conditions. Researchers analyzed two samples, each of which had a different level of accuracy. For the error rate in recognizing faces as unknown (FRR), all are 100% with a duration of 1 minute each. The conclusion of this study is to use more dataset facial images and a bright level of brightness to make it easier to recognize face